Public Opinion, Racial Bias, and Labor Market Outcomes - Kaveh Majlesi; Silvia Prina; Paul Sullivan (Institute of Labor Economics (IZA), 2022)
The effect of negative shifts in public opinion on the economic lives of minorities is unknown. We study the role of racial bias in the U.S. labor market by investigating sudden changes in public opinion about Asians following the anti-Chinese rhetoric that emerged with the COVID-19 pandemic, and associated changes in employment status and earnings. Using Current Population Survey (CPS) data from January 2019 to May 2021, we find that, unlike other minorities, Asians who worked in occupations or industries with a higher likelihood of face-to-face interactions before the pandemic were more likely to become unemployed afterwards. Consistent with a role for public opinion affecting labor market outcomes, we find that the effects are larger in magnitude in strongly Republican states, where anti-Asian rhetoric might have had more influence. Additionally, we show that, while widespread along the political spectrum, negative shifts in views of Asians were much stronger among those who voted for President Trump in 2016 and those who report watching Fox News channel.
Keywords: D70; D91; J15; P16; 330; racial bias; public opinion; minorities; unemployment; earnings